(3eONd fXQj heeGQSGJ YedjIs - (3eMeO(B, (3TheGfs ((3GdbGgQI(B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B,s, 2002)
(3GdeaGgje hGdCWQ GdfXQjI dEOGQI GdCReI,GdEYdGe hehGLgI GdCReGJ hGdchGQK,GdEYdGe hGdJUOj ddTGFYGJ,GTcGdjGJ aj eSGQ JWhQ HMhK GYdGe GdCReGJ hGdchGQK,GdUMGaI hEOGQI GdCReGJ hGdchGQK(B((3eeGQSI HMKjI(B).s
(3GdeQGLY U(B.186s
Keywords: (3GOGQI GdGReGJs; (3GdGYdGes